Case Report: Durable response to PD-1 blockade after failure of ALK-targeted therapy and chemoimmunotherapy in ALK-positive large B-cell lymphoma - Gasparini Spiandorelo, Guilherme; Alnughmush, Ahmed; Crum, Olivia; Jevremovic, Dragan; Villasboas, J. C. (Frontiers in Hematology, 2026)
BackgroundAnaplastic lymphoma kinase–positive large B-cell lymphoma (ALK+ LBCL) is an exceedingly rare and aggressive subtype of B-cell non-Hodgkin lymphoma, comprising less than 1% of all LBCL cases. These tumors often exhibit resistance to standard chemoimmunotherapy and targeted approaches, resulting in poor clinical outcomes and a median overall survival of approximately 20 months. Despite the identification of ALK rearrangements and activating mutations, effective treatment strategies remain elusive.Case presentationWe report a case of an adult diagnosed with stage IV ALK+ LBCL, confirmed via lymph node biopsy and fluorescence in situ hybridization (FISH) demonstrating ALK rearrangement in 91% of nuclei. The patient progressed through four lines of therapy, including R-CHOP, alectinib, lorlatinib with involved-field radiation, and brentuximab vedotin plus bendamustine. Comprehensive genomic profiling revealed a CLTC-ALK fusion and two ALK gain-of-function mutations (p.L1196M and p.G1202R), which are typically sensitive to lorlatinib, suggesting ALK-independent resistance mechanisms. Repeat biopsy demonstrated 20%–30% PD-L1 expression in tumor cells. With no standard options remaining, the patient elected to receive off-label nivolumab. Remarkably, despite an initial disease flare, a rapid clinical and radiological response was observed after just two cycles. As of the latest follow-up after 16 cycles, the patient remains on treatment with sustained clinical benefit and no adverse events reported.DiscussionThis case highlights the therapeutic challenges of ALK+ LBCL, including its refractoriness to both standard chemotherapy and ALK inhibitors, even in the presence of targetable mutations. The exceptional response to PD-1 blockade, possibly facilitated by acquired PD-L1 expression and an inflammatory tumor microenvironment, suggests an immunologically active tumor niche. Comparison with prior cases supports the hypothesis that PD-L1 expression, even at moderate levels, may predict responsiveness to immune checkpoint inhibitors in this rare lymphoma subtype.ConclusionThis case underscores the potential of immune checkpoint inhibition in ALK+ LBCL, particularly in patients with relapsed or refractory disease. PD-L1 testing and repeat biopsy at progression may offer critical insights for guiding therapy. Prospective studies are warranted to explore checkpoint blockade alone or in combination with targeted agents in this aggressive lymphoma.